An Assessment of EFL Students' Paragraph Writing - Yusmalinda, Yusmalinda (STBA Prayoga Padang, 2025)
This study examines how effectively English as a Foreign Language students can write paragraphs according to such factors as unity, coherence, and organization. They were the English Literature program students of the STBA Prayoga who took a Paragraph Writing subject. Paragraphs written were analysed qualitatively by close examination. Paragraphs were reread multiple times to identify key themes and concerns. This study analyzed a sample of their paragraphs and assessed them through three criteria: organization, unity, and coherence. Organising is nothing but organizing the thoughts in a logical sequence, while unity makes sure every sentence connects back to the main point. Coherence helps ideas flow smoothly within a paragraph. The results showed that students had a variety of skills in these areas. Some were able to write well-structured, unified, and smooth-flowing paragraphs, but others had a harder time keeping their ideas consistent and making their writing flow logically. These findings suggest that we need to focus on teaching strategies that help students better organize their ideas, stay on topic, and improve the flow of their writing. This study helps us understand the challenges faced by EFL learners when writing and offers some helpful ideas on how to support them in improving their paragraph writing skills in school settings.